2007
DOI: 10.1107/s0907444907019580
|View full text |Cite
|
Sign up to set email alerts
|

Using X-ray absorption spectra to monitor specific radiation damage to anomalously scattering atoms in macromolecular crystallography

Abstract: # 2007 International Union of CrystallographyPrinted in Denmark -all rights reserved Radiation damage in macromolecular crystals is not suppressed even at 90 K. This is particularly true for covalent bonds involving an anomalous scatterer (such as bromine) at the 'peak wavelength'. It is shown that a series of absorption spectra recorded on a brominated RNA faithfully monitor the extent of cleavage. The continuous spectral changes during irradiation preserve an 'isosbestic point', each spectrum being a linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…However, a negative peak in our F o Ϫ F c electron density map indicated either increased thermal motion or partial occupancy for the bromine atom. It has been shown that bromine atoms, and aryl-bromine derivatives in particular, are among the most sensitive atoms to radiation-induced x-ray damage (44). Given that neighboring ligand atoms exhibited similar B-factors and that the bromine atom is constrained to lie in the plane of the aromatic phenyl moiety, we believe that refining the occupancy of the bromine atom was justified and that the resulting reduced occupancy stemmed from x-ray damage.…”
mentioning
confidence: 89%
“…However, a negative peak in our F o Ϫ F c electron density map indicated either increased thermal motion or partial occupancy for the bromine atom. It has been shown that bromine atoms, and aryl-bromine derivatives in particular, are among the most sensitive atoms to radiation-induced x-ray damage (44). Given that neighboring ligand atoms exhibited similar B-factors and that the bromine atom is constrained to lie in the plane of the aromatic phenyl moiety, we believe that refining the occupancy of the bromine atom was justified and that the resulting reduced occupancy stemmed from x-ray damage.…”
mentioning
confidence: 89%
“…28 Chemical and structural changes induced by radiation include 29 the breakage of disulfide bonds, 30,31 the decarboxylation of glutamate and aspartate residues, [31][32][33] the loss of the hydroxyl groups of tyrosines and of the methylthio groups of methionines, 32 the reduction of metal centers, 34,35 and the decrease in the occupancy value of some heavy atoms. [36][37][38][39] Water molecules release highly reactive species, hydrogen and hydroxyl radicals, and electrons, which are capable of attacking proteins. 31,40,41 The active site of bR represented by the retinal Schiff base (SB) and its vicinity contains several aspartic acid residues and water molecules and thus is potentially susceptible to X-ray radiation damage.…”
Section: Introductionmentioning
confidence: 99%
“…1 In protein crystals, the X-ray radiation damage is manifested by progressive crystal disorder and local specific chemical changes in the protein molecule. [1][2][3][4][5][6][7][8][9][10][11] An overall crystal disorder is revealed as a degradation of crystal diffraction properties, changes in the unit cell dimensions, and an increase in the mosaicity and atomic displacement parameters (ADPs, also described as atomic temperature factors B). On the local level, chemical and structural changes induced by radiation include the disruption of disulfide bonds, 2,3 the decarboxylation of glutamate and aspartate residues, [3][4][5] the loss of the hydroxyl groups of tyrosines and of the methylthio groups of methionines, 4 the reduction of metal centers, 6,7 and the decrease of the occupancy value of some heavy atoms, [8][9][10][11] for example, Se, Br, I, and Hg.…”
Section: Introductionmentioning
confidence: 99%